2001
DOI: 10.1143/jjap.40.5962
|View full text |Cite
|
Sign up to set email alerts
|

Photoabsorption of Synthetic Silica Glass under ArF Excimer Laser Irradiation

Abstract: In-situ measurement of the transmittance change at 220 nm in synthetic silica glass under the ArF excimer laser irradiation showed three phenomenological stages: 1) initial coloring stage, 2) saturation stage where the coloring reaction equilibrates to the discoloring reaction and 3) heavy dosing stage where a rapid increase in photoabsorption occurs after an increase in the number of laser shots. The coloring rate at the initial stage depends only on the sum of the exposed laser power regardless of laser ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Messina et al [12] found that for a photon energy of 4.7 eV two photons are required to break Si-H groups and create E 0 centers. In contrast, for higher photon energies of 5.0 eV and 6.4 eV the SiH photolysis is reported to result from a 1-photon absorption process [13,14]. Furthermore, other models for long term degradation of fused silica under DUV laser irradiation take into account a breaking of Si-H bonds by single photon absorption [1,8].…”
Section: Modelmentioning
confidence: 99%
“…Messina et al [12] found that for a photon energy of 4.7 eV two photons are required to break Si-H groups and create E 0 centers. In contrast, for higher photon energies of 5.0 eV and 6.4 eV the SiH photolysis is reported to result from a 1-photon absorption process [13,14]. Furthermore, other models for long term degradation of fused silica under DUV laser irradiation take into account a breaking of Si-H bonds by single photon absorption [1,8].…”
Section: Modelmentioning
confidence: 99%
“…Several works in literature have discussed the generation mechanisms of E' in silica under laser radiation, distinguishing between single-and multi-photon processes [3][4][5][6][7][9][10][11][25][26], but most of them dealt with permanent defects, and only a few have directly observed in situ the transient E' centres originated from the Si-H precursor [10][11]25]. Only in [10] and [25], the dependence from laser energy density of the initial generation rate of transient E' centres was studied in synthetic SiO 2 exposed to KrF (5.0eV) or ArF (6.4eV) laser radiation, and reported to be respectively linear and sublinear. These results are in disagreement with the quadratic dependence found here.…”
mentioning
confidence: 99%
“…So far, photoluminescence in situ measurements have been used to clarify the generation and the decay of another defect of fundamental interest, the non-bridging oxygen hole centre (NBOHC, ≡SiO•), induced in silica by photolysis of the SiO-H bond [12,13]. At variance, although a few works have investigated E centres by monitoring optical transmittance at a fixed energy (∼5.8 eV) during irradiation [14][15][16][17], the current understanding of the generation of E centres by UV laser is mainly founded on ex situ ESR and OA measurements [18][19][20][21][22][23]. Hence, the interplay between the photo-induced creation of the E centre and its decay due to reaction with mobile hydrogen is not well understood.…”
mentioning
confidence: 99%